Clinical outcomes of a new diffractive trifocal intraocular lens with Enhanced Depth of Focus (EDOF). Issue 1 (December 2016) - Torun Acar, Banu; Duman, Erkan; Simsek, Saban
Abstract Background To evaluate the clinical outcomes after the implantation of a new trifocal diffractive intraocular lens (IOL) combined with Enhanced depth of focus (EDOF) technology. Methods The study enrolled 80 eyes of 40 patients who underwent cataract surgery with bilateral implantation of a diffractive trifocal IOL (Reviol Tri-ED) designed with a combination of enhanced depth of focus. Mean age was 52.09 ± 11.32 years (range from 45 to 70 years). Uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), uncorrected intermediate visual acuity (UIVA), corrected intermediate visual acuity (CIVA), uncorrected near visual acuity (UNVA), corrected near visual acuity (CNVA), keratometry (K), and manifest refraction spherical equivalent (MRSE) were evaluated pre- and postoperatively. The contrast sensitivity, defocus curves, and a questionnaire evaluating individual satisfaction were also estimated. Results There was a significant improvement in UDVA, CDVA, UNVA, CNVA, CIVA postoperatively. The defocus curve confirmed good visual acuity also in the intermediate distance. The postoperative MRSE was ranged from −0.75 to 0.75 diopters. Contrast sensitivity also significantly improved postoperatively. The patient satisfaction was high. Conclusion The new trifocal EDOF IOL provides visual improvement for far, intermediate, and near distances with a high level of visual quality and patient satisfaction.